Epidemiological Variations in the Global Burden of Psoriasis, an Analysis With Trends From 1990 to 2017 - Peng, Chen; Xu, Xin; Chen, Wenjuan; Li, Xingzi; Yi, Xuemei; Ding, Yangfeng; Yu, Ning; Lu, Jiajing (Frontiers in Medicine, 2021)
Background: Despite improvements in prevention, diagnosis and treatment over the past decades, psoriasis is still impact patients seriously in physical and psychosocial health. Although there were many epidemiological researches, study focused on health burden of psoriasis on global scale is still lacking. Research on this topic can highlight epidemiological variations and trends in global burden of psoriasis and lead to focused efforts to reduce the burden. Objectives: To evaluate the trends and variations in global health burden of psoriasis by year, gender, nation and socio-economic status, using disability-adjusted life years (DALYs) from the Global Burden of Disease Study. Methods: Health burden of psoriasis was evaluated by disability-adjusted life years (DALYs) which combined years lost to disability (a morbidity component) with years of life lost (a mortality component). The global and national DALYs number, crude DALYs rate and age-standardized DALYs rate were obtained from the GBD 2017 study database. The corresponding human development index (HDI) was collected from the United Nations Development Programme. Results: From 1990 to 2017, the DALYs number and crude DALYs rate due to psoriasis increased by 73% and 22%, respectively. While the age-standardized DALYs rate showed a slight increase. Both male and female showed increasing trend in burden caused by psoriasis over the past 27 years with female bearing greater psoriasis burden than male. The health burden of psoriasis was substantial unequal in geography with Gini coefficient of 0.27. The concentration indexes indicated that socioeconomic associated inequality in psoriasis burden with values of 0.22, accounting for 48.64% variance across countries (R2 = 0.4864, p < 0.001). Conclusions: Global health progress in psoriasis together with inequality in the past few decades. Female bear higher burden of psoriasis than male. Higher health burden of psoriasis is concentrated in countries with higher levels of socioeconomic development. The finding of this study highlights the global importance of psoriasis and is important in policy planning for psoriasis service on the global scale.